Tourism Cooperation under the Belt and Road Initiative: BRI and Tourism Opportunities in Phayao Province, Thailand - et. al., Piyaphong Supanyo, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The objectives of this research are 1. to study the Belt and Road Initiative (BRI) fundamental concepts in comparison with other multilateral tourism cooperative frameworks in Phayao Province, 2. to analyze the importance, benefits, and limitations of the BRI initiative, including problems, obstacles and tourism opportunities in Phayao Province according to the the Belt and Road Initiative (BRI) cooperative framework, 3. to give recommendations on policies and measures for tourism promotion of Phayao Province under the Belt and Road Initiative (BRI) cooperative framework. The research tool was used PESTEL analysis, SWOT analysis and TOWS analysis method, The population and sample group in this research work were selected by purposive sampling and consist of two main groups, which are the group including the government sectors and the private sectors of Thailand that includes Phayao Province and areas in the Lao PDR consisting of Sainyabuli province, Luang Namtha province, and areas in the China Mainland comprising of Kunming city and Xishuangbanna Dai Autonomous Prefecture. The results of the study indicated that Phayao Province has potential due to the borderline with the Lao PDR in Ban Huak, where the government has approved and promoted the temporarily permitted area at Ban Huak to be a permanent border crossing in 2018. When both countries border checkpoints had been promoted, it causes an expansion in terms of trade and investment, including more tourism. It is a gateway that connects the economic corridors of the North of Lao PDR and northern Thailand. This border-crossing route is an interconnection between Thailand via Phayao Province to Luang Prabang, where the ChinaLaos railway station is located. The Ban Huak border checkpoint journey to Luang Prabang is only 297 kilometers and can connect to southern China by the China-Laos railway. The service will be available in December 2021. This route will provide an opportunity to connect Phayao province to the New Silk Road of the 21st Century or the Belt and Road Initiative (BRI). It will enable cooperation in the field of trade, investment, and tourism between the three countries.